A numerical investigation into the effect of engine bleed on performance of a single-spool turbojet engine. - Rahman, N. U.; Whidborne, James F. (Professional Engineering Publishing, 2008)
A real time simulation model has been developed to investigate the effect of variable engine bleed on steady state and transient performance of a single-spool turbojet engine. The bleed air is to be used for flow control on the aerodynamic control surfaces of a tailless configur-ation such as the blended wing body aircraft. The engine simulation uses the inter-component volume method and runs in MATLAB/Simulink environment. Bleed effects were simulated both with and without the control of engine speed. Experimental data for the advanced micro turbine (AMT) Olympus single-spool turbojet engine was used to validate the simulation results. Under nominal bleed conditions, the results were accurate to within 5 per cent of experimental values. While for excessive engine bleeds the results were accurate to within 10 per cent. The effect of engine bleed location along the compressor length was also incorporated. A proportional + integral speed controller with slew rate limiting was implemented as an integral part of the model. The method presented here could be easily expanded for steady state and transient performance simulation of two and three spool turbojet/turbofan engines.
Keywords: turbojet simulation; component volume method; bleed flow; engine performance